Utilization of Mobile Health Technologies in Chronic Kidney Disease Management: A Scoping Review - Ardianti, Ikha; Suhamdani, Haris; Sulistyo, Angger Anugerah Hadi; Julianto, Errix Kristian; Ferawati, Ferawati (Critical Medical and Surgical Nursing Journal, 2025)
Introduction: The increasing prevalence of Chronic Kidney Disease (CKD) necessitates innovative approaches to enhance patient care and management. Mobile health (mHealth) technologies have emerged as promising tools for improving health outcomes through remote monitoring, patient engagement, and data-driven decision-making. This scoping review aims to explore the utilization of mHealth technologies in the management of CKD. Methods: A comprehensive literature search was conducted across multiple databases including PubMed/Medline, ProQuest, and DOAJ focusing on studies published in the last decade. The inclusion criteria encompassed articles that evaluated mHealth interventions specifically designed for CKD management. Key outcomes were categorized into patient adherence, clinical outcomes, patient satisfaction, and cost-effectiveness. Results: The review identified diverse mHealth applications, including mobile apps, wearable devices, and telehealth platforms, demonstrating potential benefits in improving medication adherence, monitoring disease progression, and enhancing patient-provider communication. Despite promising results, challenges such as data privacy, technological literacy, and integration with existing healthcare systems were noted. Conclusion: This review underscores the need for further research to optimize mHealth interventions and address barriers to widespread implementation in CKD management.